2017
DOI: 10.1039/c7ra00750g
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology as a powerful tool to optimize the synthesis of polymer-based graphene oxide nanocomposites for simultaneous removal of cationic and anionic heavy metal contaminants

Abstract: Nanocomposites containing graphene oxide (GO), polyethyleneimine (PEI), and chitosan (CS) were synthesized for chromium(VI) and copper(II) removal from water. Response surface methodology (RSM) was used for the optimization of the synthesis of the CS-PEI-GO beads to achieve simultaneous maximum Cr(VI) and Cu(II) removals. The RSM experimental design involved investigating different concentrations of PEI (1.0-2.0%), GO (500-1500 ppm), and glutaraldehyde (GLA) (0.5-2.5%), simultaneously. Batch adsorption experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 55 publications
1
86
0
Order By: Relevance
“…Furthermore, in many cases, Cr (VI) has shown to be reduced to Cr (III); however, the chemical pathway behind this removal and reduction has not been fully elucidated. Primarily, it was theorized to be a combination of electrostatic attraction and chemical complexation based on previous reports with other carbonaceous materials [3][4][5][6] . For instance, Chen et al reported that Cr (VI), in the form of Cr 2 O 7 2− anions bound to positively charged surfaces of wood-based powdered activated carbon (WPAC), was reduced to Cr (III), suggesting that some graphitic carbons in WPAC allowed a redox reaction to happen 5 .…”
Section: Alternative Methods Of Aqueous Chromium Removal Have Been Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in many cases, Cr (VI) has shown to be reduced to Cr (III); however, the chemical pathway behind this removal and reduction has not been fully elucidated. Primarily, it was theorized to be a combination of electrostatic attraction and chemical complexation based on previous reports with other carbonaceous materials [3][4][5][6] . For instance, Chen et al reported that Cr (VI), in the form of Cr 2 O 7 2− anions bound to positively charged surfaces of wood-based powdered activated carbon (WPAC), was reduced to Cr (III), suggesting that some graphitic carbons in WPAC allowed a redox reaction to happen 5 .…”
Section: Alternative Methods Of Aqueous Chromium Removal Have Been Ofmentioning
confidence: 99%
“…For instance, Chen et al reported that Cr (VI), in the form of Cr 2 O 7 2− anions bound to positively charged surfaces of wood-based powdered activated carbon (WPAC), was reduced to Cr (III), suggesting that some graphitic carbons in WPAC allowed a redox reaction to happen 5 . Similarly, several studies have indicated that the Cr (VI) ions in a solution can form ion complexes with graphene oxide functional groups or can be subjected to electrostatic attractions allowing easy removal from a solution by a CS-PEI-GO nanocomposite 3,4,6 . These studies showed the successful removal of Cr (VI) by carbon-based nanomaterials and polymer beads.…”
Section: Alternative Methods Of Aqueous Chromium Removal Have Been Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis is performed in terms of analysis of variance (ANOVA) in order to find significant model terms. The values of the partial probability (p value) less than 0.05 and high F value imply that the model factors are significant, whereas the p values higher than 0.1 indicate the statistically insignificant terms [31]. From Online Resource Table S1, it can be seen that the quadratic model used here has the p value of < 0.0001 indicating that the model response model is significant and there is only < 0.01% chance that the F value of the model is because of the random error.…”
Section: The Response Surface Methods Implementationmentioning
confidence: 99%
“…The relation of the design variables with the response value is derived by fitting the numerical analysis results to a second-order polynomial (Eq. 6) [31]. (6)…”
Section: Overview Of the Response Surface Modelmentioning
confidence: 99%